CULTURAL VALUES IN PARUNTUK KANA LITERATURE: A STUDY IN DATARA VILLAGE, TOMPOBULU, GOWA REGENCY - Syamhari; Ishak, Ihdiana; Hidayat, Amirullah (UIN Alauddin Makassar, 2024)
This study examines the Paruntuk Kana among the people of Datara Village, Tompobulu, Gowa Regency. This research aims to analyze the use of Paruntuk Kana among the community in Datara Village, Tompobulu, Gowa Regency, while examining the cultural values embedded within its practice in the same context. This field research employs a descriptive qualitative methodology. Data collection was conducted through interviews. The findings of this study reveal that Paruntuk Kana is a local literary work that remains prevalent in the Datara village community. Paruntuk Kana embodies the refinement of language, which is integral to the community's way of life and facilitates communication and the expression of humanitarian aspects within society. The indicators of linguistic subtlety and gentleness in Paruntuk Kana literature, as evidenced by the research, demonstrate that the diction in Paruntuk Kana plays a crucial role in addressing the audience, imbued with the values of politeness and local traditions. The cultural values embedded in Paruntuk Kana literature are local values that reflect linguistic refinement, mutual respect, honor, and the practice of life based on humanist principles.